Predictors of hospital discharge and mortality in patients with diabetes and COVID-19: updated results from the nationwide CORONADO study - Wargny, Matthieu; Potier, Louis; Gourdy, Pierre; Pichelin, Matthieu; Amadou, Coralie; Benhamou, Pierre-Yves; Bonnet, Jean-Baptiste; Bordier, Lyse; Bourron, Olivier; Chaumeil, Claude; Chevalier, Nicolas; Darmon, Patrice; et al. (Diabetologia, 2021)
Aims/hypothesis This is an update of the results from the previous report of the CORONADO (Coronavirus SARS-CoV-2 and Diabetes Outcomes) study, which aims to describe the outcomes and prognostic factors in patients with diabetes hospitalised for coronavirus disease-2019 (COVID-19). Methods The CORONADO initiative is a French nationwide multicentre study of patients with diabetes hospitalised for COVID-19 with a 28-day follow-up. The patients were screened after hospital admission from 10 March to 10 April 2020. We mainly focused on hospital discharge and death within 28 days. Results We included 2796 participants: 63.7% men, mean age 69.7 ± 13.2 years, median BMI (25th–75th percentile) 28.4 (25.0–32.4) kg/m 2 . Microvascular and macrovascular diabetic complications were found in 44.2% and 38.6% of participants, respectively. Within 28 days, 1404 (50.2%; 95% CI 48.3%, 52.1%) were discharged from hospital with a median duration of hospital stay of 9 (5–14) days, while 577 participants died (20.6%; 95% CI 19.2%, 22.2%). In multivariable models, younger age, routine metformin therapy and longer symptom duration on admission were positively associated with discharge. History of microvascular complications, anticoagulant routine therapy, dyspnoea on admission, and higher aspartate aminotransferase, white cell count and C-reactive protein levels were associated with a reduced chance of discharge. Factors associated with death within 28 days mirrored those associated with discharge, and also included routine treatment by insulin and statin as deleterious factors. Conclusions/interpretation In patients with diabetes hospitalised for COVID-19, we established prognostic factors for hospital discharge and death that could help clinicians in this pandemic period. Trial registration Clinicaltrials.gov identifier: NCT04324736 Graphical abstract